2011
DOI: 10.1111/j.1365-3156.2011.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Injury mortality in rural South Africa 2000 – 2007: rates and associated factors*

Abstract: ObjectiveTo estimate injury mortality rates in a rural population in KwaZulu-Natal, South Africa and to identify socio-demographic risk factors associated with adult injury-related deaths.MethodsThe study used population-based mortality data collected by a demographic surveillance system on all resident and non-resident members of 11 000 households. Deaths and person-years of observation (pyo) were aggregated for individuals between 01 January 2000 and 31 December 2007. Cause of death was determined by verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 19 publications
(45 reference statements)
3
41
2
Order By: Relevance
“…This compares with the study by Garrib et al, 21 which found that full-time employment was significantly associated with lower mortality in South Africa.…”
Section: Risk Factors For Injury Mortalitycontrasting
confidence: 58%
See 3 more Smart Citations
“…This compares with the study by Garrib et al, 21 which found that full-time employment was significantly associated with lower mortality in South Africa.…”
Section: Risk Factors For Injury Mortalitycontrasting
confidence: 58%
“…Studies have shown that Africa had the highest drowning death rate (13.1/100 000 PYO) and men had higher drowning death rates than women for all ages and in all regions and was more pronounced in children up to 14 years. 7 In this study, however, most of the drowning fatalities occurred in young (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and middle-aged (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) adults. In the Rufiji DSA, most of the people are engaged in subsistence farming and fishing activities with the proximity of the Rufiji River as a possible influencing factor.…”
Section: Types Of Injuriesmentioning
confidence: 66%
See 2 more Smart Citations
“…Caregivers tend to overestimate the ability of their children to act safely in traffic-for instance the ability to cross roads by themselves-but under the age of six, children are neurodevelopmentally immature and do not possess the ability and skills to adequately assess environmental dangers. [6,7,22] Community-based prevention programs are essential and should be put into practice through churches, community centres and other communal institutions to teach parents and caregivers about these topics. [22] Substance abuse was denied in all cases.…”
Section: Discussionmentioning
confidence: 99%